LONGITUDINAL MOTION MODEL SIMULATION AND CONTROL SYSTEM DESIGN OF HYBRID UNDERWATER GLIDER - Latifah, Ayu
Autonomous underwater vehicle or commonly abbreviated as AUV is a vehicle that can move under water, which is also known as an unmanned undersea vehicle (UUV). One type of AUV is a hybrid underwater glider (HUG) where the vehicle is designed in such a way as to be able to carry out missions in water with less power consumption so that it can last a long time in carrying out missions. In this research mathematical design is carried out to produce modeling in the longitudinal plane of the HUG vehicle which will be tested based a simulation using the MATLAB / Simulink. The parameters used in the model for longitudinal plane are obtained by computational fluid dynamics (CFD) method so that it has been simulated with various movements according to the mission of the vehicle. In the simulation, a nonlinear model is used which is given input as variations value of the actuator that modeled as input for longitudinal plane including the main thruster as surge actuator, moving mass for pitch and buoyancy engine movements to make the vehicle sink where the simulation is an open loop system that derived translation position, speed and rotation. PID Controller are designed for steer and depth control using inner and outer loop method from controller design so that the vehicle can manuveuring to desire position.